ISSUES OF LEGAL REGULATION OF ORGANIC AGRICULTURAL PRODUCTION IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT: COMPARATIVE ANALYSIS OF OF THE LEGISLATION OF THE REPUBLIC OF KAZAKHSTAN AND FOREIGN COUNTRIES (Journal of actual problems of jurisprudence, 2025)
The organic sector is a rapidly developing area of the agricultural industry. Organic food products are in high demand in the domestic and global food markets. Kazakhstan's food production does not go beyond global trends. However, the legislative framework for the production of organic products, their labeling, storage and quality control in the country requires deregulation and further clarification of the legislative aspects of the organic sector of agricultural production.The subject of the study is the legal mechanism of organic agricultural production in order to fulfill Kazakhstan's international obligations in the field of sustainable development. Several aspects of the development of organic agricultural production in the context of sustainable development can be distinguished. First, it is dangerous to withdraw from circulation in the event of overexploitation of lands, for which agricultural producers are paid appropriate compensation. Second, it is an incentive for environmentally friendly production. Third, it is a measure to limit the use of agrochemicals until taxes are introduced. Fourth, it is an incentive for tree planting, regulation of water flows and general land restoration, however, the latter is carried out very carefully. Thus, recognition of the importance of wetlands as an element of natural ecosystems leads to a very careful approach to their drainage. Fifth, it is a policy of preserving historical landscapes, including buildings, historical heritage. Sixth, it includes a policy of developing and preserving some mountain slopes and less developed agricultural areas, where the population is mainly leaving.The authors, studying the legal means of conducting organic agricultural production, legislate the principle of sustainable development in agricultural production, performs a comparative analysis of the legislation of foreign countries, Recommendations for improving the land legislation of the Republic of Kazakhstan, examination of environmentally friendly products in accordance with world standards to provide the consumer with quality products, regarding the attraction of new innovations, certification of new organic products, as well as legislative consolidation of the principle of sustainable development in agricultural production, on amendments to the norms of the Land Code of the Republic of Kazakhstan.Keywords: Sustainable development, legal protection of the environment, greening, greening of agricultural production, agriculture, organic products, ecosystem.